Polygamy in Islam and Its Relevance to Law No. 1 of 1974 Concerning Marriage - Aryani, Winda Intan; Adly, Muhammad Amar; Yazid, Imam (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Polygamy is a topic that always invites polemics in society, especially in the context of households. Although polygamy existed long before Islam, Islam accommodates this practice with several limitations and conditions, especially in terms of justice for wives. Problems that often arise in the practice of polygamy include abuse of rights and obligations, physical and psychological violence, and negative impacts on women and children. This study aims to understand more deeply the legal perspective of polygamy, especially according to the views of Buya Hamka and Nasr Hamid Abu Zayd. This study uses a normative juridical method with a literature study approach, utilizing primary legal materials such as the Al-Qur'an interpretation book by Hamka and Abu Zayd, as well as secondary legal materials from Islamic law literature and related laws. The analysis was carried out by describing, recording, and interpreting data to understand the differences in the views of the two figures regarding the law of polygamy. The results of the study show that there are uniqueness and differences in the thoughts of Hamka and Abu Zayd that can influence the implementation of polygamy law in Indonesia. This study provides important insights into the dynamics of polygamy law in the modern context and its contribution to legal policy in Indonesia.